\(h\)-strongly \(E\)-convex functions - Marian, Daniela (Rev. Anal. Numér. Théor. Approx., 2011)
Starting from strongly \(E\)-convex functions introduced by E. A. Youness, and T. Emam, from \(h\)-convex functionsintroduced by S. Varošanec and from the more general conceptof \(h\)-convex functions introduced by A. Házy we define and study \(h\)-strongly \(E\)-convex functions. We study some properties of them.